The Point-Rating Scale for Determining Treatment Tactics in Patients With Adhesive Small Bowel Obstruction - B. V. Sigua; V. P. Zemlyanoy; B. P. Filenko; P. A. Kotkov; D. Kh. Kalandarova; A. A. Kozobin (Неотложная медицинская помощь, 2021)
Relevance. The most practiced method of treating patients with acute intestinal obstruction - urgent surgical intervention - does not guarantee remission, contributing to the progression of morphological changes in the abdominal cavity. From this perspective, a shift in emphasis towards the planned surgical treatment of patients with adhesive disease with the use of the existing anti-adhesive methods after conservative resolution of the intestinal passage disorders looks like a promising direction.Aim of the study. Improving the results of patients with acute adhesive intestinal obstruction treatment by developing a point-rating scale that allows to highlight groups of patients who are prone to conservative resolution of intestinal passage disorders episode, and, thereby, reduces the proportion of urgent interventions.Material and methods. The analysis of the 125 patients treatment results (retrospective group) admitted with symptoms of acute adhesive intestinal obstruction was carried out. On this basis, the point-rating scale was developed including a number of factors that have certain value in terms of predicting the probability of conservative therapy success. Subsequently the developed scale was applied in 170 patients (prospective group) as part of treatment tactics implementation aimed at maximally conservative resolution of adhesive intestinal obstruction without negative effect on the immediate results of patients operated in later periods.Results. The developed point-rating scale made it possible to reduce the frequency of urgent interventions among patients with signs of acute adhesive intestinal obstruction (from 79.2% to 57.6%) due to longer conservative measures — 18.1±17.2 and 11,2±8.7 hours in prospective and retrospective groups, respectively). There was no negative impact on the frequency of resection interventions (12.2 and 16.1% in the prospective and retrospective groups) as well as postoperative complications and overall mortality.Conclusions. The developed point-assessment scale made it possible to stratify patients in accordance with the probability of conservative therapy success and to justify its continuation for more than 12 hours in low-risk patients. The obtained results allow us to recommend the proposed scale for use in clinical practice.